GEDUNG SENI DAN BUDAYA BANYUMAS DENGAN PENDEKATAN LOKALITAS DI PURWOKERTO - Kinanti, Kirana Wahyu; Pitana, Titis Srimuda; Yuliani, Sri (Universitas Sebelas Maret Surakarta, 2015)
Design and planningof Banyumas art and cultural building are based on the need of art and cultural facility in Banyumas Regency. There have been many art andcultural facilities in Banyumas, but no one are spesifically design for art and cultural activity. Because of these reason, those cultural faciliies can not be used efisienly. Art and cultural building, whichis located in Purwokerto City,also needs to have a touch of Banyumas Cultural nuance as part of its integrated design. The goal of Art and Cultural Building designing and planing is get an Art and Cultural Building with Banyumasn Nuance by using Locality Prespective as an Approach. This locality prespective will be used along the design and planing and can be seen at groundplan, siteplan, massing, Landscape, and structure. The result is a design of art and cultural building with many facilities such as artist and cultural observer secretariat, auditorium, galery, amphitheatre, pendhapa, office building, and mousque.Keywords: Art centre, Culture, Defined Cultural of Banyumas, Locality